2014
DOI: 10.1007/s00228-014-1705-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of one-time apple juice ingestion on the pharmacokinetics of fexofenadine enantiomers

Abstract: These results suggest that OATP2B1 plays an important role in the stereoselective pharmacokinetics of fexofenadine and that one-time apple juice ingestion probably inhibits intestinal OATP2B1-mediated transport of both enantiomers. In addition, this study demonstrates that the OATP2B1 inhibition effect does not require repeated ingestion or a large volume of apple juice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 32 publications
3
30
1
4
Order By: Relevance
“…Additionally, a previous clinical study found that a single ingestion of AJ significantly decreases the AUC 0e24 for (R)-and (S)-fexofenadine by 49% and 59%, respectively [31], while the present single-intake GFJ study showed that the AUC 0e24 values of (R)-and (S)-fexofenadine decreased by 39% and 52%, respectively (Table 1). A recent in vitro study reported that co-incubation with AJ reduces *P < 0.05, **P < 0.01, ***P < 0.001, between control phase and GFJ phase.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Additionally, a previous clinical study found that a single ingestion of AJ significantly decreases the AUC 0e24 for (R)-and (S)-fexofenadine by 49% and 59%, respectively [31], while the present single-intake GFJ study showed that the AUC 0e24 values of (R)-and (S)-fexofenadine decreased by 39% and 52%, respectively (Table 1). A recent in vitro study reported that co-incubation with AJ reduces *P < 0.05, **P < 0.01, ***P < 0.001, between control phase and GFJ phase.…”
Section: Discussionmentioning
confidence: 66%
“…In our recent in vitro study [31], uptake into oocytes injected with OATP2B1 cRNA was higher for (R)-fexofenadine than (S)-fexofenadine. Consistent with these results, the present in vivo analysis demonstrated that the plasma concentration of (R)-fexofenadine was higher than the corresponding (S)-enantiomer during the control phase (Fig.…”
Section: Figmentioning
confidence: 96%
See 3 more Smart Citations